Celebrating a Heterogeneous Community: The Ebibi Festival of the Epe People - Babatunde Olanrewaju Adebua (Yoruba Studies Review, 2021)
The Ijebu people and their rituals have been the subject of several scholarly studies, but existing work concentrates on the larger and more prominent Ijebu communities. Little attention has been paid to the more obscure communities, particularly those in the riverine areas. This article examines the coastal community of Epe, divided into an Ijebu and a Lagos "town," through a study of the Ijebu Ebibi festival. It pays attention to the origin and plural nature of the community, to participation in the various communal events, and it offers a comparison between the coastal and upland Ijebu communities. Other areas of focus include the aesthetics and didacticism of oral performances, moral codes and communal self-reliance. The article concludes that Ebibi is a festival that delineates community both through bringing together multiple performances, styles, and social groups in Ijebu Epe, by highlighting differences between different Ijebu communities that celebrate Ebibi, and by confirming the boundary between Ijebu and Lagos Epe.